Analysis of Factors Influencing Customer Behavioral Intentions to Use Mobile Banking - Bustami, Edwin; Budaya, Indra; Regen, Ronal; Zasriati, Masrida (International Journal of Artificial Intelligence Research, 2022)
This study aims to examine and investigate knowledge, beliefs, convenience, risk, and culture that directly and indirectly influence attitudes, convenience and usability regarding mobile banking and Behavioral Intention to use Jambi mobile banking services. This research uses survey and verification methods. The sample used is 400 units. Data analysis using Path Analysis. The results of the study show that knowledge, comfort, and risk have a direct and significant effect on attitudes; risk and culture have a direct and significant impact on convenience; risk and culture have a direct and significant effect on usability; knowledge, convenience, risk, cultural attitudes, convenience, and usability have a direct and significant impact on Behavioral Intention; knowledge, comfort, and risk have an indirect and significant effect on Behavioral Intention through attitudes; culture has an indirect and significant effect on Behavioral Intention through convenience; knowledge, comfort, and culture have an indirect and significant impact on Behavioral Intention through usability. The study results recommend that future management should increase and maintain customer knowledge, trust, convenience, risk, culture, attitudes, convenience, and usability of mobile banking utilizing direct or indirect education through multi-media.